Producción de biosurfactantes de bacterias con potencial para degradar hidrocarburos - Navarrete Carriola, Diana V; Rivera, Gildardo; Mendez Alvarez, Domingo; Ortiz Perez, Eyra L; Paz González, Alma D (Universidad Autónoma de Nuevo León, 2023)
Memorias